2022
DOI: 10.18203/2320-1770.ijrcog20220173
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial histopathology patterns in women with abnormal uterine bleeding

Abstract: Background: Abnormal uterine bleeding is the most common gynaecological condition for which many women seek medical opinion. Evaluation of these women requires careful investigation into the cause and nature of bleeding with a main focus to exclude organic pathology, especially genital malignancies. Endometrial biopsy is one such intervention which is of immense value in categorizing the conditions. Aims and objectives of current study were to analyse endometrial histology patterns in women with AUB.Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A total of 360 cases of endometrial samples with a clinical diagnosis of AUB were analysed.In this study, AUB was commonly seen among perimenopausal age group(58.3%) which is in concordance with Rajani Vaidya et al, 1 Vijayaraghavan et al, 3 Jagadalekunda et al 5 Sajitha et al, 6 Sharma et al, 7 Khan et al 8 Majority of the cases of AUB were of multiparous women (57.8%) which is a similar finding in other studies. 3,[5][6][7][8][9][10][11][12][13][14] In the present study, high body mass index (BMI) was observed in women with hyperplasia and malignancy. Out of 94 cases of hyperplasia, 55 cases were overweight, 15 cases were obese.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A total of 360 cases of endometrial samples with a clinical diagnosis of AUB were analysed.In this study, AUB was commonly seen among perimenopausal age group(58.3%) which is in concordance with Rajani Vaidya et al, 1 Vijayaraghavan et al, 3 Jagadalekunda et al 5 Sajitha et al, 6 Sharma et al, 7 Khan et al 8 Majority of the cases of AUB were of multiparous women (57.8%) which is a similar finding in other studies. 3,[5][6][7][8][9][10][11][12][13][14] In the present study, high body mass index (BMI) was observed in women with hyperplasia and malignancy. Out of 94 cases of hyperplasia, 55 cases were overweight, 15 cases were obese.…”
Section: Discussionmentioning
confidence: 93%
“…3,[5][6][7][8][9][10][11][12][13] Functional causes (64.2%) of AUB are more common than organic causes (35.8%) in this study which is in concordance with study done by Sharma et al, 7 Vijayaraghavan et al, 3 Dwivedi et al, 9 Prathipa et al, 10 J Bindhuja et al, 12 Neha Khanam et al 15 Normal cyclical endometrium patterns are commonly seen in the present studywhich is similar to other studies. [3][4][5][6][7][8][9][10][11][12][13][14][15] Proliferative phase (34.7%) was the most common followed by secretory phase (18.9%) among all age groups of women in the present study.Similar findings were observed by Vijayaraghavan et al, 3 Jagadale Kunda et al, 5 Sharma et al 7 Disordered proliferative endometrium was seen in 5.83% of cases. Majority of the cases were in the age group of 18-40 years.…”
Section: Discussionmentioning
confidence: 99%